The influences of porus acusticus internus on ethnicity and importance in preoperative and intraoperative approaches. - Sekerci, Rahime; Ogut, Eren; Keles-Celik, Nigar (Surgical & Radiologic Anatomy, 2021)
Purpose: The influences of porus acusticus internus (PAI) on ethnicity and differences between populations have not been investigated so far. Therefore, we performed this study to elucidate further the relationship between the different morphologies of PAI and ethnicity and to discuss their effects on surgery. Methods: One hundred twenty dry adult human temporal bones (61 male, 59 female) were investigated in the study. Their horizontal diameter (HD), vertical diameter (VD), shape, prevalence of the shapes of PAI, and the distance from the sulcus for the sigmoid sinus (SSS), sulcus for superior petrosal sinus (SSPS), and jugular foramen (JF) of dry Turkish temporal bones were recorded. Results: Forty-three (35.8%) elliptical (or transverse) and 77 (64.1%) oval (or round) PAI were detected in the Turkish dry temporal bones. On both sides, round PAI were identified more frequently than elliptical ones (32; 26.6% (left); 39; 32.5% (right)) (p < 0.05). There was a similarity between the Indian and Turkish dry temporal bones in terms of distance from the PAI to the SSPS (7–8 mm) and SSS (19–20 mm) (p = 0.01) and prevalence of morphology of PAI (oval and elliptical) (p = 0.04, p < 0.05). Conclusion: The findings of the present study provided a detailed understanding of the preoperative and intraoperative identification of different morphologies of PAI and ethnicity. The ethnicity might contribute to morphology of the PAI and it can be explain the similar forms and distances between the various ethnic populations.